Impulse Buying pada Produk Fashion Brand Jilbrave di Shopee sebagai Dampak dari Scarcity dan Hedonic Shopping Motivation - Salwa Az Zahra; Wawan Hermawan; Dinna Charisma; R. Ela Sulastri (Yayasan Jompa Research and Development, 2026)
This study aims to analyze the effect of Scarcity and Hedonic Shopping Motivation on Impulse Buying on Jilbrave fashion consumers. The data collection technique in this research is questionnaires and literature study. The population in this study were Jilbrave consumers in Shopee. The number of samples taken in this study were 180 samples. The sampling method used in this study is non-probability sampling using the purposive sampling technique. The data processed using the SEM-PLS method with SmartPLS 4.1.1.8 software. Testing the coefficient of determination produces findings where the variables scraity and hedonic shopping motivation are able to effect impulse buying on Jilbrave fashion consumers in the shopee by 74,1%. While the remaining 25,9% is effect by other variables. The result of this study indicate that Hedonic Shopping Motivation has a dominant effect on Impulse Buying, Scarcity has an effect on Impulse Buying.